Predictive factors and outcomes of respiratory syncytial virus infection among patients with respiratory failure - Tongyoo, Surat; Naorungroj, Thummaporn; Laikitmongkhon, Jakkrit (Frontiers in Medicine, 2023)
Introduction Respiratory syncytial virus (RSV) infection is an emerging infectious disease. However, the impacts of RSV infection among patients with respiratory failure have not been identified. Objective This study investigated the 28-day mortality and clinical outcomes of RSV infection in patients with respiratory failure. Methods This retrospective study enrolled patients admitted with respiratory failure and requiring mechanical ventilator support for more than 24 h at Siriraj Hospital, Bangkok, Thailand, between January 2014 and July 2019. Respiratory samples of the patients were examined to identify RSV infections. The primary outcome was 28-day mortality. Results Respiratory syncytial virus infection was identified in 67 of the 335 patients with respiratory failure enrolled in this study. There were no significant differences in the following baseline characteristics of the patients with and without RSV infection: mean age (72.7 ± 12.7 years vs. 71 ± 14.8 years), sex (male: 46.3% vs. 47.4%), comorbidities, and initial Murray lung injury scores (1.1 ± 0.8 vs. 1.1 ± 0.9). The 28-day mortality was 38.8% (26/67) for the RSV group and 37.1% (99/268) for the non-RSV group (p = 0.79). However, the RSV group had significantly higher proportions of bronchospasm (98.5% vs. 60.8%; p < 0.001), ventilator-associated pneumonia (52.2% vs. 33.8%; p = 0.005), and lung atelectasis (10.4% vs. 3.0%; p = 0.009) than the non-RSV group. Conclusion Among the patients with respiratory failure, the 28-day mortality of patients with and without RSV infection did not differ. However, patients with RSV infection had an increased risk of complications, such as bronchospasm, ventilation-associated pneumonia, and lung atelectasis.